2012
DOI: 10.5539/jsd.v5n4p165
|View full text |Cite
|
Sign up to set email alerts
|

How Important is Oil in Nigeria’s Economic Growth?

Abstract: This study assesses the importance of oil in the development of the Nigerian economy in a multivariate VAR model over the period

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 30 publications
3
74
0
Order By: Relevance
“…The similar types of studies are conducted for various countries and found the natural resource hypothesis to be valid, i.e. Papyrakis and Gerlagh (2007) study the U.S. states, Akinlo (2012) studies the Nigerian oil case. Beck (2011) studies the link between natural resource abundance and financial development.…”
Section: Review Of Relevant Literaturementioning
confidence: 96%
“…The similar types of studies are conducted for various countries and found the natural resource hypothesis to be valid, i.e. Papyrakis and Gerlagh (2007) study the U.S. states, Akinlo (2012) studies the Nigerian oil case. Beck (2011) studies the link between natural resource abundance and financial development.…”
Section: Review Of Relevant Literaturementioning
confidence: 96%
“…However, government expenditure appears to be the main source for economic growth in the long run, and in the short run, variations in government expenditure are generally derived by oil revenue shocks. Similarly, Akinlo () found out a long‐run relationship among five sub sectors, i.e. Agriculture, Manufacturing, oil, building and construction, and trade and services in Nigeria over the sample period, which is an indication that increased oil activities, could impact on the other sectors.…”
Section: Review Of Related Studiesmentioning
confidence: 88%
“…This was evident as crude oil production increased from 1.9 million barrels in 1958 to 152.4 barrels in 1966; from 395.7 million barrels in 1970 to 600.1 and 845.5 million barrels in 1975 and 1979 respectively. The output continued to increase from 711.3 million barrels, 742.3 million barrels and 2.15 billion barrels in 1996, 1998 and 2012 respectively (Akinlo, 2012).…”
Section: Introductionmentioning
confidence: 99%